Reestruturação e expansão das Universidades Federais: a adesão da UFSCar ao REUNI - Canhete, Aparecida Regina Firmino (2024)
The Federal University of São Carlos (UFSCar), throughout its slightly over 50 years of operation, has undergone profound changes that have greatly impacted its actions, resulting in its way of being, producing and presenting itself, and particularly within the context of Brazilian federal higher education institutions and society in general. These changes have essentially resulted from a process of decision-making and democratization of decisions, within the scope of its Superior Councils, which have been happening since the establishment of the first Superior Council. Currently the University Council, ConsUni, the highest deliberative body at the University, composed of representatives from all categories of the university community, has its decisions taken through a democratic and participatory process. Thus, based on the assumption that many decision-making processes impacted the Institution itself, Brazilian higher education and society, this study has the objective of broadly document how UFSCar’s decision, taken by the University Council, in adhering to the Program for Support for Restructuring and Expansion Plans of Federal Universities (REUNI) occured, seeking to understand the causes of internal reactions to its implementation. Furthermore, it aims to contribute to the recording of history and the pressing need to preserve the memory of UFSCar, given that 66% of teaching and technical-administrative employees have spent less than 15 years at the Institution. Given the unitary nature of the object studied, the methodology used was the case study, through bibliographical and documentary research, the latter being fundamental for the development of the theme and understanding of the internal manifestations that occurred in the process of joining UFSCar to REUNI, as well as understand the national scenario involving the Program launched by the federal government. This research, in another instance, will contribute to studies in Science, Technology and Society (STS), highlighting the importance of interdisciplinarity, and its potential to understand and record the history of the Institution, preserving its institutional memory, in addition to contributing to future research related to the topic.